Femur Rotation and Patellofemoral Joint Kinematics: A Weight-Bearing Magnetic Resonance Imaging Analysis - Souza, Richard B.; Draper, Christie E.; Fredericson, Michael; Powers, Christopher M. (The journal of orthopaedic and sports physical therapy, 2010)
Controlled laboratory study using a cross-sectional design. To compare patellofemoral joint kinematics, femoral rotation, and patella rotation between females with patellofemoral pain (PFP) and pain-free controls using weight-bearing kinematic magnetic resonance imaging. Recently, it has been recognized that patellofemoral malalignment may be the result of femoral motion as opposed to patella motion. Fifteen females with PFP and 15 pain-free females between the ages of 18 and 45 years participated in this study. Kinematic imaging of the patellofemoral joint was performed using a vertically open magnetic resonance imaging system. Axial-oblique images were obtained using a fast gradient-echo pulse sequence. Images were acquired at a rate of 1 image per second while subjects performed a single-limb squat. Measures of femur and patella rotation (relative to the image field of view), lateral patella tilt, and lateral patella displacement were made from images obtained at 45 degrees , 30 degrees , 15 degrees , and 0 degrees of knee flexion. Group differences were assessed using a mixed-model analysis of variance with repeated measures. When compared to the control group, females with PFP demonstrated significantly greater lateral patella displacement at all angles evaluated and significantly greater lateral patella tilt at 30 degrees , 15 degrees , and 0 degrees of knee flexion. Similarly, greater medial femoral rotation was observed in the PFP group at 45 degrees , 15 degrees , and 0 degrees of knee flexion when compared to the control group. No group differences in patella rotation were found. Altered patellofemoral joint kinematics in females with PFP appears to be related to excessive medial femoral rotation, as opposed to lateral patella rotation. Our results suggest that the control of femur rotation may be important in restoring normal patellofemoral joint kinematics. J Orthop Sports Phys Ther 2010;40(5):277-285, Epub 12 March 2010. doi:10.2519/jospt.2010.3215.